Effectiveness of the Viet Nam produced, mouse brain-derived, inactivated Japanese encephalitis vaccine in Northern Viet Nam. - Florian Marks; Thi Thu Yen Nguyen; Nhu Duong Tran; Minh Hong Nguyen; Hai Ha Vu; Christian G Meyer; Young Ae You; Frank Konings; Wei Liu; Thomas F Wierzba; Zhi-Yi Xu (Public Library of Science (PLoS), 2012)
Background Japanese encephalitis (JE) is a flaviviral disease of public health concern in many parts of Asia. JE often occurs in large epidemics, has a high case-fatality ratio and, among survivors, frequently causes persistent neurological sequelae and mental disabilities. In 1997, the Vietnamese government initiated immunization campaigns targeting all children aged 1-5 years. Three doses of a locally-produced, mouse brain-derived, inactivated JE vaccine (MBV) were given. This study aims at evaluating the effectiveness of Viet Nam's MBV. Methodology A matched case-control study was conducted in Northern Viet Nam. Cases were identified through an ongoing hospital-based surveillance. Each case was matched to four healthy controls for age, gender, and neighborhood. The vaccination history was ascertained through JE immunization logbooks maintained at local health centers. Principal findings Thirty cases and 120 controls were enrolled. The effectiveness of the JE vaccine was 92.9% [95% CI: 66.6-98.5]. Confounding effects of other risk variables were not observed. Conclusions Our results strongly suggest that the locally-produced JE-MBV given to 1-5 years old Vietnamese children was efficacious.